Concepts Are Restructured During Language Contact: The Birth of Blue and Other Color Concepts in Tsimane’-Spanish Bilinguals - Malik-Moraleda, Saima; Mahowald, Kyle; Conway, Bevil R.; Gibson, Edward (Psychological Science, 2023)
Words and the concepts they represent vary across languages. Here we ask if mother-tongue concepts are altered by learning a second language. What happens when speakers of Tsimane’, a language with few consensus color terms, learn Bolivian Spanish, a language with more terms? Three possibilities arise: Concepts in Tsimane’ may remain unaffected, or they may be remapped, either by Tsimane’ terms taking on new meanings or by borrowing Bolivian-Spanish terms. We found that adult bilingual speakers ( n = 30) remapped Tsimane’ concepts without importing Bolivian-Spanish terms into Tsimane’. All Tsimane’ terms become more precise; for example, concepts of monolingual shandyes and yụshñus ( green or blue, used synonymously by Tsimane’ monolinguals; n = 71) come to reflect the Bolivian-Spanish distinction of verde ( green) and azul ( blue). These results show that learning a second language can change the concepts in the first language.